الأحكام العامة للعقد بين المعايير الشرعية للأيوفي والقانون المدني البحريني:دراسة تحليلية مقارنة = General provisions of contract between AAOIFI Sharia standards and Bahraini Civil Law: a comparative analytical study - Zakariyah, Habeebullah; Alshaikh, Hamad Farooq (2022)
The research sheds light on a comparison between the provisions of the Bahraini Civil Law and the Sharia standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) with regard to the most important provisions of the contract, such as the pillars of the contract and the form of the contract. The research aims to clarify the most important points of agreement and differences between the civil law and the Sharia standards in relation to Islamic financial transactions to identify the size of the gap between them, in preparation for conducting further studies in this regard due to the subjection of financial transactions applied in Islamic banks in the Kingdom of Bahrain to Sharia standards and civil law provisions. The research relied on the qualitative approach and comparative analytical description. The research concluded that there are many points of agreement between the two references and that the points of difference in the contract and the meeting are not essential, and the researcher recommends conducting more comparative studies between local laws and Sharia standards with regard to Islamic financial formulas and products and re-conducting a comprehensive study of Sharia standards to examine the gaps and weaknesses Through which Islamic banks and their contracts may be affected, the researcher also recommends that the (AAOIFI) Institutions issue sharia standards for contract theory, contract foundations and what is related to it, and to refer in the civil law to the reference of Islamic banks to the sharia standards affiliated with (AAOIFI).